Data-driven discoveries on widespread contamination of freshwater reservoirs by dominant antibiotic resistance genes. (1st February 2023) - Guo, Zhao-Feng; Boeing, Wiebke J.; Xu, Yao-Yang; Borgomeo, Edoardo; Liu, Dong; Zhu, Yong-Guan
Highlights: Data-driven framework shows distribution, factors, and pollution hotspots of ARGs. Geospatial differences exist in the classes and abundance of ARGs in reservoirs. Reservoir characteristics have a strong influence on ARG pollution. ARGs in reservoir waters and sediments exhibited different pollution hotspots. Data sharing is encouraged to improve data accessibility and depth of research. Abstract: The propagation of antibiotic resistance genes (ARGs) in freshwater reservoirs threatens ecosystem security and human health, and has attracted increasing attention. A series of recent research articles on ARGs provides a unique opportunity for data-driven discoveries in this emerging field. Here, we mined data from a total of 290 samples from 60 reservoirs worldwide with a data-driven framework (DD) developed to discover geographical distribution, influencing factors and pollution hotspots of ARGs in freshwater reservoirs. Most data came from Asia and Europe where nine classes of ARGs were most frequently detected in reservoirs with multi-drug resistance and sulfonamide resistance genes prevailing. Factors driving distribution of reservoir ARGs differed between reservoir waters and sediments, and interactions among these factors had linear or nonlinear enhancement effects on the explanatory power of ARG distribution. During the cold season, small-sized reservoir waters rich in organic carbon, mobile genetic elements (MGEs) and antibiotics had a higher pollution potential of ARGs; during the spring drought, sediments in large reservoirs located in densely populated areas were more conducive to dissemination of ARGs due to their richness in antibiotics and MGEs. Thus, distribution pattern of ARG pollution hotspots in reservoir waters and sediments varies greatly depending on the differences of internal and external factors. From the "One Health" perspective, this widespread contamination of freshwater reservoirs by ARGs we discovered through the DD framework should be a push to promote integrated research across regions and disciplines. Especially the human - food-chain - ecosystem interface needs an improved understanding of ARG contamination mechanisms and targeted monitoring and evaluation systems should be developed to maintain all ecosystem services in freshwater reservoirs as well as to safeguard human health. Graphical abstract: Image, graphical abstract